Leadership assignation for knowledge sharing amongst Mara technical colleges directors - Asran Abdullah, M. H. (2015)
This study explores the nature of knowledge sharing practices in Mara technical colleges and identifies the leadership engagement of the Mara directors in supporting the knowledge sharing session in their own respective technical colleges. In addition, the study also examines various strategical approach used for knowledge sharing and factors that influence the knowledge sharing activities within Mara technical colleges. This study employed case study qualitative design approach and data were obtained using series of interviews with three directors and six instructors from selected Mara technical colleges. Previous studies indicate that informal session were much preferred by the instructors eventhough Mara technical colleges have their own formal system of knowledge sharing sessions as part of their human development training session. In investigating whether the Mara directors have practically performed their formal designation as knowledge sharing enabler, instructors mentioned in the interviews that their directors give support and encouragement for any knowledge sharing sessions and the directors also play a significant role as role model with having networking sessions with other college's directors. As far as influencing factors are concerned, time constraints and individuals attitudes slowed the process of knowledge sharing in Mara technical colleges.